2018
DOI: 10.1038/s41567-018-0228-3
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved collapse and revival of the Kondo state near a quantum phase transition

Abstract: K 8 K. We thus observe a scenario of quasiparticle

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 34 publications
10
27
0
2
Order By: Relevance
“…In this Letter, we resolve this puzzle by separately measuring the Kondo and the crystal-electric-field (CEF) contributions to the Fermi volume using time-resolved terahertz spectroscopy [18] and temperature-dependent dynamical mean-field theory (DMFT) calculations. Timedomain terahertz spectroscopy has been recently developed as a method particularly sensitive to the QP dynamics in strongly correlated electron systems [18]. We find that for the heavy-fermion compound CeCu 6−x Au x , the spectral weight contributing to the large Fermi volume at high temperatures is accounted for by the CEF satellite resonances of the Ce 4f orbitals, while the low-temperature behavior is controlled by the Kondo resonance, in particular near the QPT at x = 0.1.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this Letter, we resolve this puzzle by separately measuring the Kondo and the crystal-electric-field (CEF) contributions to the Fermi volume using time-resolved terahertz spectroscopy [18] and temperature-dependent dynamical mean-field theory (DMFT) calculations. Timedomain terahertz spectroscopy has been recently developed as a method particularly sensitive to the QP dynamics in strongly correlated electron systems [18]. We find that for the heavy-fermion compound CeCu 6−x Au x , the spectral weight contributing to the large Fermi volume at high temperatures is accounted for by the CEF satellite resonances of the Ce 4f orbitals, while the low-temperature behavior is controlled by the Kondo resonance, in particular near the QPT at x = 0.1.…”
mentioning
confidence: 99%
“…We observe that this signal does not appear in the Pt reference, has a reproducible, nonmonotonic temperature dependence (analyzed below), and vanishes in all measured time traces below T = 5 K. We use this temperature dependence to separate signal (ii) from the single-particle reflex (i): We (b) Evolution of the background-subtracted CEF signal (−2.5 to +2.5 ps) and the Kondo signal (+3.5 to +8.5 ps) as the temperature decreases from 290 to 2 K. The green-shaded region depicting the envelope of the Kondo signal is a solution of the nonlinear rate equation of Ref. [18] describing the relaxation of the terahertz-excited heavy-fermion system with a single local orbital. Trivial delayed reflexes originating from the terahertz generation crystal or the cryostat windows have been identified at times t > 10 ps [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, time-resolved terahertz (THz) spectroscopy has proven to be a powerful tool to coherently probe collective excitations in solids, in particular the correlation dynamics in heavy-fermion systems. We have shown that upon excitation with low-energy THz radiation, part of the correlated Kondo state can be extinguished and resurges back with a distinct temporal separation from the instantaneous conductionelectron response [28]. In order to identify this delayed response within the time traces, the following conditions must be fulfilled: (1) The energy scale of the Kondo correlated states, i.e., the Kondo lattice temperature T * K , should be well separated from the single-particle binding energy of the 4 f electrons in the heavy-fermion system (Kondo regime).…”
Section: Introductionmentioning
confidence: 99%
“…The terahertz (THz) spectral region has a long standing interest for a wide range of applications such as imaging [1], telecommunication [2,3], spectroscopy [4], as well as thickness measurements [5]. It is also indispensable in current fundamental research, e.g., in the study of superconductivity [6,7], quasiparticles such as magnons [8], heavy fermions [9] and in dynamically induced phase transitions [10]. However, a lack of compact, powerful and efficient THz radiation sources has hindered a wide-spread deployment of such applications.…”
Section: Introductionmentioning
confidence: 99%